Quality of Romantic Attachment, Forgiveness, and Altruism in Parents of Children with Special Needs and Parents of Regular School Children - Bagher Ghobari Bonab; Farzaneh Motamedi; Fatemeh Shabizade; Shohreh Sadeghi (Universitas Ahmad Dahlan, 2016)
Abstract The aim of the current study was to investigate the relationship between forgiveness, quality of romantic attachment with altruism in parents of children with special needs and regular school children. In this study, 275 individuals (144 parents of regular school children using cluster sampling and 131 parents of children with special needs using available sampling[procedure) were selected. In this study Enright forgiveness inventory (Enright, 1977), Adult Attachment Inventory (Hazen& Shaver, 1987), and altruism (Ashton & et al., 1998); were used. Analysis of data was performed by using multiple regression analysis. Results of the analysis revealed that in parents of regular school children there was a significant negative correlation between insecure attachment to spouse and cognitive, emotional and behavioral domain of forgiveness. Whereas in parents of exceptional children there was a significant negative correlation between insecure attachment to spouse and cognitive and behavioral dimensions of forgiveness. Multiple regression analysis revealed that in mothers of children with special needs and regular school children quality of attachment to the spouse was a significant variable in determining the forgiveness (cognitive, behavioral and emotional dimension of forgiveness). The quality of attachment is a significant variable in determining the magnitude of forgiveness. Keyword: forgiveness, quality of attachment to spouse, altruism, exceptional parents, regular school children’s mother.